2022
DOI: 10.1039/d1bm01591e
|View full text |Cite
|
Sign up to set email alerts
|

DNase I functional microgels for neutrophil extracellular trap disruption

Abstract: Non-fouling DNase I conjugated microgel provide a novel biohybrid platform to disrupt Neutrophil extracellular traps (NETs) and can be used as a non-thrombogenic coating for reduction of NET-mediated inflammation and microthrombi formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 84 publications
0
25
0
Order By: Relevance
“…[ 17 ] This includes the display or release of inhibitors of coagulation factors and antiplatelet agents, release of nitric oxide and digestion of neutrophil extracellular trap, and display of thrombolytic agents. [ 18 ] In spite of the improved hemocompatibility, passive as well as active coatings fail to completely inhibit surface‐induced coagulation. On the one hand, passive antifouling coatings fail as soon as very small amounts of coagulation factors manage to adsorb and self‐amplification mechanisms becomes activated resulting in the propagation of coagulation and clot formation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] This includes the display or release of inhibitors of coagulation factors and antiplatelet agents, release of nitric oxide and digestion of neutrophil extracellular trap, and display of thrombolytic agents. [ 18 ] In spite of the improved hemocompatibility, passive as well as active coatings fail to completely inhibit surface‐induced coagulation. On the one hand, passive antifouling coatings fail as soon as very small amounts of coagulation factors manage to adsorb and self‐amplification mechanisms becomes activated resulting in the propagation of coagulation and clot formation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies that focused on patients with ARDS secondary to COVID-19 found that aerosolized pulmozyme had positive effects in relieving acute respiratory failure and improving patients’ outcomes [ 28 , 29 ]. However, rh-DNase I was metabolized rapidly, whereas the pulmonary inflammation was persistent, which made it difficult for therapeutic effects to be maintained for a long time [ 29 , 30 ]. Thus, novel therapies targeting NETs-related DNA might be a promising treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several works which are under experimental research or preclinically used include degrading already formed NETs and blocking the aberrant formation of NETs (shown in Table 3). DNase I is one of the endonucleases that cleave DNA, resulting in the collapse of the web-like structure, and is commonly used as a NETs inhibitor [140]. Previous studies reported that Dnase I could improve diabetic wound healing through the clearance of NETs [141] and mechanistically research revealed that Dnase I exerted its function mainly by improving inflammation resolution, reactivating epithelial regeneration-related signaling pathways, and attenuating the cumulation of reactive oxygen species (ROS) [142].…”
Section: Potential Treatment Strategies For Inhibiting Netsmentioning
confidence: 99%